2021
DOI: 10.1088/1742-6596/1751/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Physical Parameters of Water Quality in Real-Time Based on Arduino

Abstract: In this study, a physical parameter measurement system has been implemented for real-time monitoring of Arduino-based water quality for catfish farming applications. This system aims to detect physical parameters of water quality such as pH and water temperature using the Analog pH Meter and DS18B20 sensors. Data were collected by inserting the two sensor probes into the catfish pond water medium. The results showed that the system can detect parameters, display and store sampling data on the Visual Studio 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…III, the level of error and accuracy of DS18B20 sensor measurements reached an error value of 5.26%, with an accuracy of 94.734%. In another study [58] reported an error of 0.29%; [59] achieved a 5% error; [60] reported a 0.2% error; [61] error is 0.829%; [62] had a 3.00% error with accuracy below 85%. In the study [63], the sensor accuracy ranged from 95% to 99%.…”
Section: Testing the Error And Accuracy Of Ds18b20 Sensor Measurementsmentioning
confidence: 99%
“…III, the level of error and accuracy of DS18B20 sensor measurements reached an error value of 5.26%, with an accuracy of 94.734%. In another study [58] reported an error of 0.29%; [59] achieved a 5% error; [60] reported a 0.2% error; [61] error is 0.829%; [62] had a 3.00% error with accuracy below 85%. In the study [63], the sensor accuracy ranged from 95% to 99%.…”
Section: Testing the Error And Accuracy Of Ds18b20 Sensor Measurementsmentioning
confidence: 99%
“…Teknologi informasi memberikan dampak yang baik bagi perkembangan teknologi yang semakin canggih. Salah satu contohnya adalah system komunikasi serat optik [1]- [3]. Serat optik adalah saluran transmisi cahaya yang terdiri dari jenis serat optik plastik dan kaca.…”
Section: Pendahuluanunclassified
“…e water is sucked from the water reservoir and is fed into the process level tank with the use of a pump and transmitted to the pipeline system. Different setups for level recording, flow recording, and pressure recording are made to record the real-time data from the water distribution system [35,36] as shown in Figures 3, 4, and 5. e water distribution system is pilot scaled and used for real-time data monitoring based on pressure and flow sensors' feedback.…”
Section: Experimental Hardware For Water Distribution Systemmentioning
confidence: 99%